2016
DOI: 10.1038/srep28808
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-tubulin enhanced renal tubular cell proliferation and tissue repair but reduced cell death and cell-crystal adhesion

Abstract: Adhesion of calcium oxalate (CaOx) crystals on renal tubular epithelial cells is a critical event for kidney stone disease that triggers many cascades of cellular response. Our previous expression proteomics study identified several altered proteins in MDCK renal tubular cells induced by CaOx crystals. However, functional significance of those changes had not been investigated. The present study thus aimed to define functional roles of such proteome data. Global protein network analysis using STRING software r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…To study renal physiology and pathophysiology, cell lines are frequently grown on culture plates, Transwell, chemotaxis chamber, etc. Numerous studies have shown that these convenient and simple culture systems can be applied to study sophisticated mechanisms of kidney diseases 2 5 . In the case of Transwell culture system, its specialized feature for polarized cell cultivation that can separate upper and lower chambers allows independent access to both distinct fluid compartments and offers advantages for evaluation of cellular functions relating to apico-basolateral trans/paracellular transports 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…To study renal physiology and pathophysiology, cell lines are frequently grown on culture plates, Transwell, chemotaxis chamber, etc. Numerous studies have shown that these convenient and simple culture systems can be applied to study sophisticated mechanisms of kidney diseases 2 5 . In the case of Transwell culture system, its specialized feature for polarized cell cultivation that can separate upper and lower chambers allows independent access to both distinct fluid compartments and offers advantages for evaluation of cellular functions relating to apico-basolateral trans/paracellular transports 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Scratch assay was performed according to the standard protocol 44,45 , with slight modifications. Briefly, MDCK cells were seeded in a six-well culture plate (Corning Inc., Corning, NY) at a density of 4 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney stones are a kind of global disease. Treatments exist, but the recurrence rate of kidney stones remains high, and no effective prevention methods have been found 13. The main components of calcium oxalate kidney stones are calcium oxalate monohydrate (COM) and calcium oxalate dihydrate.…”
Section: Introductionmentioning
confidence: 99%